2022
DOI: 10.3390/rs14194962
|View full text |Cite
|
Sign up to set email alerts
|

Desert Soil Salinity Inversion Models Based on Field In Situ Spectroscopy in Southern Xinjiang, China

Abstract: Soil salinization is prominent environmental issue in arid and semi-arid regions, such as Xinjiang in Northwest China. Salinization severely restricts economic and agricultural development and would lead to ecosystem degradation. Finding a method of rapidly and accurately determining soil salinity (SS) is one of the main challenges in salinity evaluation, saline soil development, and utilization. In situ visible and near infrared (Vis-NIR) spectroscopy has proven to be a promising technique for detecting soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Although the ACO algorithm had the highest number of feature bands, the average improvement capability (an improvement of 0.45) was lower than that of the PSO algorithm (an improvement of 0.48), which may be due to the interference of redundant information in the feature bands selected by the ACO algorithm. In contrast, Wang et al concluded that the accuracy improvement of SA was superior to that of PSO, which may be attributable to the fact that the initial temperature level affected the rate of convergence; therefore a reasonable selection of initial parameters is needed [47]. The feature bands based on the SPA algorithm were mainly distributed in the 400 to 607 nm range.…”
Section: Model Validationmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the ACO algorithm had the highest number of feature bands, the average improvement capability (an improvement of 0.45) was lower than that of the PSO algorithm (an improvement of 0.48), which may be due to the interference of redundant information in the feature bands selected by the ACO algorithm. In contrast, Wang et al concluded that the accuracy improvement of SA was superior to that of PSO, which may be attributable to the fact that the initial temperature level affected the rate of convergence; therefore a reasonable selection of initial parameters is needed [47]. The feature bands based on the SPA algorithm were mainly distributed in the 400 to 607 nm range.…”
Section: Model Validationmentioning
confidence: 95%
“…Among the three nonlinear machine learning models, XGBoost had a better anti-fitting function considering the complexity of the model, which improved the generalizability of the model. BPNN has a strong nonlinear mapping ability, which is attributable to its self-learning, self-organization, and self-adaptation ability, which could effectively make up for the deficiency of the linear model [47]. Compared with the first two models, RF is only a tree model.…”
Section: Effects Of Modeling Strategies On Estimation Accuracymentioning
confidence: 99%
“…Land surface cover data: We selected the normalized difference vegetation Index (NDVI) as an environmental variable to characterize surface vegetation cover [44][45][46]. Saltaffected soils with crust formation have high reflectance in the near-infrared (NIR) band and have been widely used in remote sensing studies of soil salinization [47][48][49][50]. Therefore, we chose it as an environmental variable for inferring soil salinity.…”
Section: Environmental Variables Datamentioning
confidence: 99%
“…In order to accurately estimate soil salinity, Mohamed et al [13] used the joint data to predict soil salinity and used the BPNN to select features that can help farmers in areas affected by soil salinization to better manage planting procedures and improve their land quality. Wang et al [14] used the CNN and SVM to predict soil salinity, which shows that the models have great potential for measuring. In light of this, feature selection algorithms emerge as a vital tool for identifying and choosing critical environmental covariates with a significant impact on salinity.…”
Section: Introductionmentioning
confidence: 99%